Facilitating Better Outcomes: How Positive Species Interactions Can Improve Oyster Reef Restoration - Reeves, Simon E.; Renzi, Julianna J.; Fobert, Emily K.; Silliman, Brian R.; Hancock, Boze; Gillies, Chris L. (Frontiers in Marine Science, 2020)
Over 85% of the world’s oyster reefs have been lost in the past two centuries, triggering a global effort to restore shellfish reef ecosystems and the ecosystem services they provide. While there has been considerable success in reestablishing oyster reefs, many challenges remain. These include: high incidence of failed restoration, high cost of restoration per unit area, and increasing stress from climate change, which now imperils many restored reefs. In order to leverage our past successes and progress the field, we must increase restoration efficiencies that not only reduce cost per unit area, but also increase the resilience of restored ecosystems. To address this need, we review the literature associated with the structure and function of oyster reef ecosystems to identify key positive species interactions (i.e. those species interactions where at least one partner benefits and no partners are harmed) that, if systematically incorporated into restoration planning, have the potential to greatly increase restoration outcomes and success. We classified positive inter- and intraspecific feedbacks between oysters and organisms associated with oyster ecosystems into the following seven functional categories: 1) physical reef creation, 2) positive density dependence, 3) refugia from physical stress, 4) refugia from biological stress, 5) biodiversity enhancement, 6) improvement of settlement, and 7) long-distance facilitation. We discuss each category of interaction positive feedback and how restoration practitioners can use knowledge of such processes to alter management and enhance restoration success. We propose that systematic incorporation of positive species interactions that generate these feedbacks into restoration practice may enhance ecological services provided by restored reefs and increase restoration success.